(untitled) (Fiep Bulletin - online, 2015)
This course is organized by the Belgian Federation of Physical Education under the international patronage of the F.I.E.P. The interesting programme of this Course has specially in view to compare divers methods presented by professors of several countries; it will be published in detail in the next issue of this bulletin. Mr. Walter Dufour professor at the university of Brussels will assume its direction.